مباحث الجرح والتعديل عند الإمام الزركشي: دراسة تحليلية - Fettane, Amar; Mochammad Sahid, Mualimin (Institute of Hadith Research, INHAD, Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
يعد الإمام الزركشي أحد العلماء الموسوعيين الذين لهم مشاركة في جميع علوم الإسلام المعروفة في زمنه. وتضم قائمة مؤلفاته كتباً في القرآن وعلومه، والحديث، والفقه، والأصول، واللغة، كما أنها تضم كتبا تناول فيها بعض المظاهر الاجتماعية في زمنه. والغاية من هذا البحث المختصر هو الوقوف على آراء هذا الإمام فيما يتعلق بفن من فنون الحديث خاصة، ألا وهو علم الجرح والتعديل في نطاقه النظري التأصيلي. ولقد استقرأ الباحث كتبه المتوفرة وجمع منها كلامه حول هذا الفن، ثم تعرض لها بالتحليل والمقارنة والنقد. والذي يظهر أن الإمام الزركشي رحمه الله تعالى رغم كون شهرته أكثر في الدراسات القرآنية والأصولية، إلا أن وقوف الباحث على المؤلفات الحديثية لهذا الإمام بينت مشاركته الهامة في ميدان الحديث وعلومه، ليس نقلا فقط، بل مذاكرةً، وتحليلاً وشرحاً، وترجيحاً ونقداً. ********************************************************** Al-Imam al-Zarkashi is a prominent figure in the history of Islamic legal thought during the eighth century AH. He lived for a short period; however, he produced a rich intellectual legacy which covers many areas of Islamic as well as Arabic language sciences. Although al-Zarkashi is known by scholars and researchers by his significant contributions in jurisprudence more than any other area, this study attempts to shed light on other areas in which his contribution is not negligible. In Hadith sciences, he devoted many pieces of his works, there is similar significance with other fields that built al-Zarkashi’s scientific legacy. The research relies mainly on surveying Zarkashi’s works in the standards of narrator’s evaluation and approaching them analytically to demonstrate their relevance and scientific value. The findings of the research can be summarized as follows: in his works, many views, analyses, and critics are considered original in both style of presentation and demonstration. His contribution relies not only on his personal view and analysis but also on the way he used the available sources at his time. In fact, his writings helped to keep and transmit many views and opinions of his precedents and contemporaries which might not be available today.